2015
DOI: 10.1007/s11145-015-9605-9
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ reported practices for teaching writing in England

Abstract: To date there have been no systematic studies examining the ways in which teachers in England focus and adapt their teaching of writing. The current study addresses this gap by investigating the nature and frequency of teachers’ approaches to the teaching of writing in a sample of English primary schools, using the ‘simple view of writing’ as a framework to examine the extent to which different aspects of the writing process are addressed. One hundred and eighty-eight staff from ten different schools responded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
56
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 42 publications
8
56
1
Order By: Relevance
“…Seventy‐five percent of middle school Chinese teachers in this study indicated that their college preparation was inadequate. This is consistent with prior studies showing that most teachers in middle school and other grades share this opinion about college preparation (Brindle et al., ; Dockrell et al., ; Gilbert & Graham, ; Graham et al., 2104; Ray et al., ), although this is not always the case (Cutler & Graham, ; Veiga Simão et al., ).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Seventy‐five percent of middle school Chinese teachers in this study indicated that their college preparation was inadequate. This is consistent with prior studies showing that most teachers in middle school and other grades share this opinion about college preparation (Brindle et al., ; Dockrell et al., ; Gilbert & Graham, ; Graham et al., 2104; Ray et al., ), although this is not always the case (Cutler & Graham, ; Veiga Simão et al., ).…”
Section: Discussionsupporting
confidence: 90%
“…This first prediction was supported because teachers in each city evidenced clear variability in their responses to almost all items involving preparation to teach writing, beliefs about writing, and writing instructional practices. Such variability has been common in prior surveys in China (Hsiang & Graham, ) and other locations around the world (e.g., De Smedt et al., ; Dockrell et al., ; Graham et al., ; Veiga Simão et al., ).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…On the other hand, the main focus of second language writing instruction has been the exclusive use of independent writing practices and is well evident in previous research (Bitchener, Young, & Cameron, 2005;Dockrell, Marshall, & Wyse, 2015;Miao, Badger, & Zhen, 2006;Storch 2005;Wigglesworth & Storch, 2012;Yasuda, 2015).…”
Section: Introductionmentioning
confidence: 63%